Determinants of a Case Series of Hand Foot Mouth Disease (HFMD) in Children Under the Age of 5 Years - Almas Nada Salsabila; Farah Azwinda; Mutia Nabila Nur Afra; Destasari Tri Hartanti; Lady Aqnes Kurniawati; Julia Elviethasari; Tamara Aulia Fakhrinnisa; Arya Fadlilah Pradana; Budi Utomo; Shifa Fauziyah (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2024)
Background: Hand Foot Mouth Disease (HFMD) is an acute infectious disease. The epidemic of HFMD has been reported in some countries in the Pacific region, every three years in America, and almost every year in China. This study is conducted to determine risk factors that correlate with HFMD in children under five years old in Dusun Sengkrakan, Lawang. This study is a cross-sectional study with an analytical observational approach.Method: The sample size was determined by total sampling, including 54 mothers with children under five years old in Dusun Sengkrakan, Lawang. The result was then analyzed with a statistical package for the social science (SPSS).Results: This study shows that there is a significant correlation between children’s age (p = 0.012) and HFMD occurrence, meanwhile, sex, birth weight, gestational age, exclusive breastfeeding, number of siblings in the house, and mother’s age have no significant correlation with HFMD occurrence. Children's age is the most dominant factor among other independent variables [p = 0.017; OR 2.849 (95% CI: 1.203 – 6.750)]. The result of this study is expected to raise public awareness of promotive and preventive measures against HFMD for the public purpose of preventing HFMD outbreaks in Indonesia